Pengungkapan Opini Audit Going Concern Melalui Kualitas Audit Sebagai Variabel Intervening - Adhynia Velsi (Journal of Business and Economics (JBE) UPI YPTK, 2019)
The purpose of this study was to examine the effect of financial factors (profitability and company growth) and non-financial factors (audit lag) on ​​going concern audit opinions through audit quality as an intervening variable. The object of the research is mining companies listed on the Indonesia Stock Exchange for the period 2016 to 2020. The population used in this study are mining companies listed on the Indonesia Stock Exchange for the period 2016 to 2020, which are 49 companies. The type of data used in this research is quantitative data using purporsive sampling method. The sample in this study were 23 mining companies listed on the Indonesia Stock Exchange. The results of this study indicate that: (1) profitability has no effect on audit quality. (2) company growth has no effect on audit quality. (3) audit lag has no effect on audit quality. (4) profitability has no effect on going concern audit opinion. (5) company growth has no effect on going concern audit opinion